PERCEPTIONS OF MUSLIM CONVERTS ON THE INFLUENCE OF THE MEDIA IN COMBATING ISLAMOPHOBIA : A PHENOMENOLOGY STUDY IN SABAH AND SARAWAK - Salinayanti, Salim; Noor Azam, Othman (Penerbit Universiti Sains Malaysia, 2025)
This study examines Muslim converts’ perceptions in a Muslim-majority country of the influence of mass media (television and radio) and social media (Facebook and YouTube) in addressing Islamophobia within the framework of Stig Hjarvard’s mediatisation concept. Mediatisation, according to Hjarvard, is the understanding of how media increasingly shape and influence various aspects of society, transforming the way individuals and institutions engage with the world. This qualitative study employed a phenomenological approach in order to understand Muslim converts’ lived experiences and their perspectives on the media strategies in combating Islamophobia. The participants were 20 Muslim converts living in Sabah and Sarawak city centres. Data were collected through individual interviews and analysed using the thematic analysis and interpretive phenomenological approach (IPA). The study discovered the presence of Islamophobia in Sabah and Sarawak. It is found that Muslim converts in Sabah and Sarawak perceive the media, including both Islamic mass media and social media, as influential tools in combating Islamophobia, with a focus on dispelling myths, promoting understanding and engaging in interfaith dialogue. This research expands Hjarvard’s concept of media influence in countering Islamophobia through Islamic da’wah. In conclusion, this study emphasises the media’s vital role as an alternative information source, aiding in educating about Islam and potentially decreasing or eliminating Islamophobia in Malaysia and the global setting.